Increased uptake and improved outcomes of bowel cancer screening with a faecal immunochemical test: results from a pilot study within the national screening programme in England. Issue 9 (7th June 2016) - Moss, Sue; Mathews, Christopher; Day, T J; Smith, Steve; Seaman, Helen E; Snowball, Julia; Halloran, Stephen P
Abstract : Background: The National Health Service Bowel Cancer Screening Programme (BCSP) in England uses a guaiac-based faecal occult blood test (gFOBt). A quantitative faecal immunochemical test (FIT) for haemoglobin (Hb) has many advantages, including being specific for human blood, detecting Hb at a much lower concentration with a single faecal sample and improved uptake. Methods: In 2014, a large comparative pilot study was performed within BCSP to establish the acceptability and diagnostic performance of FIT. Over a 6-month period, 40 930 (1 in 28) subjects were sent a FIT (OC-SENSOR) instead of a gFOBt. A bespoke FIT package was used to mail FIT sampling devices to and from FIT subjects. All participants positive with either gFOBt or FIT (cut-off 20 µg Hb/g faeces) were referred for follow-up. Subgroup analysis included cut-off concentrations, age, sex, screening history and deprivation quintile. Results: While overall uptake increased by over 7 percentage points with FIT (66.4% vs 59.3%, OR 1.35, 95% CI 1.33 to 1.38), uptake by previous non-responders almost doubled (FIT 23.9% vs gFOBt 12.5%, OR 2.20, 95% CI 2.10 to 2.29). The increase in overall uptake was significantly higher in men than women and was observed across all deprivation quintiles. With the conventional 20 µg/g cut-off, FIT positivity was 7.8% and ranged from 5.7% in 59–64-year-old women to 11.1% in 70–75-year-old men. Cancer detection increased twofold and that for advanced adenomas nearly fivefold. Detection rates remained higher with FIT for advanced adenomas, even at 180 µg Hb/g. Conclusions: Markedly improved participation rates were achieved in a mature gFOBt-based national screening programme and disparities between men and women were reduced. High positivity rates, particularly in men and previous non-respondents, challenge the available colonoscopy resource, but improvements in neoplasia detection are still achievable within this limited resource.